Potential of utilizing Calotropis procera flower biomass as a renewable source of energy - R.K. Meena, Mala Rathore* and (Journal of Phytology, 2010)
SUMMARY Calotropis procera, a laticiferous arid plant has been identified as a potential petrocrop. It is a potential plant for bioenergy and biofuel production in semi arid regions of the country. Calotropis procera is an erect much branced shrub, 2-3 m high with leaves about 10-13 cm wide by 17-19 cm long. It is a soft wooded evergreen perennial bush and with its conspicuous purplish pink flowers it is one of the most common and impressing plants in arid region. The plant grows well up to 2 meters, and its roots are said to reach down to a depth of even 3 meters. Almost all the parts of Calotropis procera yield hydrocarbons. Biocrude obtained from this plant is reported to be a rich source of tri-terpenoid type of hydrocarbons. Hexane extract of different parts of Calotropis procera viz. whole plant, stem, leaves and pods have been evaluated. Flowers of Calotropis procera contribute significantly to the total biomass of the plant. The flowers are available throughout the year. They are bitter, digestive, astringent, anthelmintic, tonic, anti-inflammatory, spasmolytic, stomachic, hepatoprotective & antioxidant and useful in cold, asthma, catarrh, anorexia, inflammations, tumours. Present work highlights the biomass and biocrude from flowers of Calotropis procera. The biomass of flowers was evaluated for different seasons shows maximum fresh biomass of 799.10 gm in summer season. The dried biomass of C. procera flowers was subjected to non-polar (petroleum ether 60-80) and polar (methanol) solvent extraction to check its extractibilities. The total extractive yield was found maximum in monsoons 4.5 % (petroleum ether extract) and 27.9 % (methanol extract). The flower biomass of Calotropis procera can, therefore, be exploited as a potential source of bioenergy. Key words: Calotropis procera, flowers, extractability, biomass, bioenergy <span style="font-weight: normal; font-size: 7pt; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Mala Rathore and R.K. Meena. Potential of utilizing Calotropis procera flower biomass as a renewable source of energy. Â J Phytol 2/1 (2010) 78-83.